Development Students Worksheet Using Ethnomathematics-based CTL Approach on SLETV Subject Material for Grade X - Mursalina, Ditya; Marhamah, Marhamah; Retta, Allen Marga (Jurusan Matematika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Sema, 2021)
This study aims to produce worksheets using an ethnomatematic based CTL approach on SLETV material that is valid and practical. This type of research and development is R&D. The ADDIE development model consists of: analyze, design, development, implementation, evaluation. However, this research is limited to the implementation stage for individual trials (one to one) and small group trials. The results of this study were obtained from the aspects of validity and practicality. a) the validity aspect is obtained based on 3 validators with assessment aspects based on content, construct, and language with the first validator score of 84.61% in the